Hegel's Pluralism as a Comedy of Action. Issue 3 (December 2019) - Yeomans, Christopher
Abstract: Our reception of Hegel's theory of action faces a fundamental difficulty: on the one hand, that theory is quite clearly embedded in a social theory of modern life, but on the other hand most of the features of the society that gave that embedding its specific content have become almost inscrutably strange to us (e.g., the estates and the monarchy). Thus we find ourselves in the awkward position of stressing the theory's sociality even as we scramble backwards to distance ourselves from the particular social institutions that gave conceptualized form to such sociality in Hegel's own opinion. My attempt in this article is to make our position less awkward by giving us at least one social-ontological leg to stand on. Specifically, I want to defend a principled and conceptual pluralism as forming the heart of Hegel's theory of action. If this view can be made out, then we will have a social-ontological structure that might be filled out in different ways in Hegel's time and our own while simultaneously giving real teeth to the notion that Hegel's theory of action is essentially social.